X/XYq - mosaicism and mixed gonadal dysgenesis. Issue 4 (August 1977) - Yunis, E; Silva, R; Ramirez, E; Nossa, M A
Abstract : A non-fluorescent Y chromosome was observed in a phenotypic male with 45, X/46, XYq-mosaicism and mixed gonadal dysgenesis. Q-banding of the father's chromosomes showed a normally fluorescent Y. Measurements of the Y chromosomes in the father and the patient showed a significant difference in length. Evidence for translocation of the Y fluorescent segment to another chromosome was lacking in the present case.